Analisis Valuasi Startup Panak.id Menggunakan Scorecard Method - Windari, Ni Putu Rani; Putra, I Gede Juliana Eka; Putri, I Gusti Agung Pramesti Dwi (Jurnal Ilmiah Teknologi Informasi Asia; Vol 17 No 1 (2023): Volume 17 Nomor 1 (8)DO - 10.32815/jitika.v17i1.891, 2023)
In this study, a valuation was carried out on a startup in Bali, namely Panak.id. Panak.id is a startup engaged in crowdfunding and livestock marketplaces. This valuation is carried out with the aim that the results of the valuation can be used as a reference in negotiations with investors when seeking funding or used as material for evaluating the company's performance. This study calculates the valuation value of Panak.id's startup on its crowdfunding business model, namely "Bisnak". Valuations are carried out using the Scorecard method with assessments based on non-financial factors and then comparing them with companies engaged in similar sectors. There are 7 elements assessed in the Scorecard method, namely Strength of Entrepreneur and Team, Size of the Opportunity, Product/Technology, Competitive Environment, Marketing/Sales/Partnerships, Need for Additional Investment, and Other Factors, with an Extension SUM score of 4.425. Based on the assessment carried out, the Panak.id startup valuation value obtained through calculations using the Scorecard method is IDR 1,496,250,000. Keywords : Scorecard method , Startup, Startup Valuation